Lamotrigine can be beneficial in patients with Dravet syndrome. (22nd September 2014) - Dalic, Linda; Mullen, Saul A; Roulet Perez, Eliane; Scheffer, Ingrid
<x xml:space="preserve">Abstract</x> Dravet syndrome, a severe infantile epilepsy syndrome, is typically resistant to anti‐epileptic drugs (AED). Lamotrigine (LTG), an AED that is effective for both focal and generalized seizures, has been reported to aggravate seizures in Dravet syndrome. Therefore, LTG is usually avoided in Dravet syndrome. We describe two adults and a child with Dravet syndrome in whom LTG resulted in decreased seizure duration and frequency. This benefit was highlighted in each patient when LTG was withdrawn after 6 to 15 years, and resulted in an increased frequency of convulsive seizures together with longer seizure duration. A 25‐year‐old male required hospital admission for frequent seizures for the first time in 7 years, 6 weeks after ceasing LTG. Reintroduction of LTG improved seizure control, suggesting that in some patients with Dravet syndrome, LTG may be beneficial.